INDUCED MUTATION BY GAMMA RAYS IRRADIATION TO INCREASE CHILLI RESISTANCE TO BEGOMOVIRUS - Gaswanto, Redy; Syukur, Muhamad; Purwoko, Bambang Sapta; Hidayat, Sri Hendrastuti (AGRIVITA, Journal of Agricultural Science, 2016)
Begomovirus infection has a significant impact of lowering chilli yield in Indonesia. A constraint of narrow genetic variability of chilli in Indonesia has made the mutation breeding program as a solution worth-pursuing in increasing the genetic variability. The objective of this study was to determine the LD50 point for each of the five irradiated chilli genotypes and the optimum dose of gamma irradiation in inducing chilli resistance to Begomovirus and other improved agronomical traits. The study was conducted in the Indonesian Vegetable Research Institute (IVEGRI) at Cikole-Lembang, elevation 1,200 m above sea level, from March to December 2013. Split plot design was used with genotype as main factor (Kencana, Lembang-1, SSP, Tanjung 2, Seloka) and irra-diation dosage as sub-factor (0, 200, 400, 600, 800 Gy). All treatments were replicated three times. The results showed that LD50 points of the five irradiated chilli genotypes were in the range of 422.64-629.68 Gy. There were some chilli genotypes in the population of M2 that had high coefficient variance genetic (CVG) and broad sense heritability (h2bs) value for disease incu-bation time. This could be used as resistance parameter to Begomovirus and improvement parameter of several agronomical traits.